2020
DOI: 10.1002/hpm.3081
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the screening: The need for health systems intervention for prevention and management of sickle cell disease among tribal population of India

Abstract: Globally, sickle cell disease (SCD) is one of the major public health problems. In India, it is more prevalent in tribal communities. Tribal communities are socio‐economically disadvantaged and constitute 8.6% of India's population. The health and health care seeking of these communities is very poor. Though efficacious interventions are available to manage SCD, they are not reaching these people and no comprehensive programme is in place. The objective of this analysis is to demonstrate the burden of SCD amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…The screening of SCD, particularly in remote tribal areas is almost absent. 9 This pilot study is part of a multicentric study to develop an effective intervention model for SCD patients in tribal communities through the government health care system. 10 This study aimed to establish a model of screening, and to report the prevalence of SCD and trait among children aged 1-5 years.…”
Section: Prevalence Of Sickle Cell Disease Among Children Of Tribal Population In India: Feasibility Of Screening At Community Level In Lmentioning
confidence: 99%
“…The screening of SCD, particularly in remote tribal areas is almost absent. 9 This pilot study is part of a multicentric study to develop an effective intervention model for SCD patients in tribal communities through the government health care system. 10 This study aimed to establish a model of screening, and to report the prevalence of SCD and trait among children aged 1-5 years.…”
Section: Prevalence Of Sickle Cell Disease Among Children Of Tribal Population In India: Feasibility Of Screening At Community Level In Lmentioning
confidence: 99%
“…With regard to SCD, various control programs have been in operation in India for an extended period of time. However, due to the lack of an organizational referral system and standard treatment guidelines for the management of SCD, most of these programs are limited to the screening of patients [40]. It has been observed that most patients seek treatment only when they have an acute sickle cell crisis.…”
Section: Sickle Cell Disease: a Life-threatening And Highly Morbid Disordermentioning
confidence: 99%
“…In 2016, the Indian government aimed to increase the accessibility of hydroxyurea in district hospitals located in high-prevalence areas and issued guidelines for the prevention and control of hemoglobinopathies [51]. However, due to implementation gaps, the program could not be initiated in the majority of states, particularly in tribal areas [40]. Recently, a draft policy was prepared, which advocates for the improvement of SCD treatment centers in all districts and ensures a free supply of hydroxyurea and penicillin to low-income patients [52].…”
Section: The Way Forwardmentioning
confidence: 99%
“…Despite the huge burden of SCD in the country, particularly among vulnerable communities like tribes, the control programmes are still in draft format, and no health systems approach exists to deal with the burden (Government of India 2021, Raman et al 2021). The primary health care system, which primarily caters to the preventive and curative services to the tribal populations, totally ignored SCD, and there are no treatment or referral systems in most tribal areas (Geethakumari et al 2021). However, there is growing attention that leads to the development of an SCD programme (Government of India 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For accessing modern health care, people seek advice from their traditional healers. Thus, traditional healers are essential in generating people's awareness and acceptance of health care services (Geethakumari et al 2021).…”
Section: Introductionmentioning
confidence: 99%